EFEKTIVITAS PENERAPAN MODUL AJAR BERBASIS GRAPHIC ORGANIZER PADA MATERI KALOR DAN PERPINDAHANNYA - Jihandris, Egidius Elvin; Maria S, Haratua Tiur; Hidayatullah, Muhammad Musa Syarif (Universitas Tanjungpura, 2024)
The purpose of this study is to find out the effectiveness of a teaching module using graphic organizers on student learning outcomes. This study is an experimental study. The research design adopts the preexperimental design of